IMPLEMENTASI KURIKULUM MERDEKA TERHADAP PENGUATAN KARAKTER SISWA SEKOLAH DASAR DI KOTA SERANG - Andriani Sariwardani; Suhendi; Arif Hidayat; Ema Nurmawaty; Iin Kurnia; Dwi Saktiawan; Setiyanto; Rusyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Merdeka Curriculum in strengthening the character of elementary school students in Serang City through the Project for Strengthening the Profile of Pancasila Students (P5). The research method employed is descriptive qualitative, with data collection techniques including observation, interviews, and documentation across several public elementary schools in Serang. The results indicate that the implementation of the Merdeka Curriculum provides flexibility for teachers to integrate character values—such as independence, mutual cooperation (gotong royong), and Banten’s local wisdom—into the learning process. The primary challenges faced include the adaptation of teaching modules and inconsistent character assessment methods. Overall, however, the Merdeka Curriculum is effective in enhancing students' ethical awareness and social behavior within the school environment.